Design and synthesis of Atglistatin derivatives as adipose triglyceride lipase inhibitors. (26th June 2017) - Jin, Jiyu; Huang, Suling; Wang, Lei; Leng, Ying; Lu, Wei
Abstract : Adipose triglyceride lipase (ATGL) is a rate‐limiting enzyme that mobilizes fatty acids from cellular triglyceride stores. Metabolic syndrome, which refers to a group of abnormalities that occur together and increase the risk of coronary artery disease, stroke, type 2 diabetes, and cachexia, can be treated using ATGL‐specific inhibitors. Atglistatin (1 ) is the first small‐molecule inhibitor of ATGL. In this study, we designed and synthesized 29 Atglistatin derivatives and evaluated their inhibition of forskolin‐stimulated lipolysis in 3T3‐L1 adipocytes as an indicator of their potential to inhibit ATGL in adipose tissues. Among all the tested Atglistatin analogs, we previously found that the thiourea compound9e showed potent ATGL inhibitory activity in vitro, which was much stronger than that of Atglistatin, and its inhibitory activity in vivo was similar to that of Atglistatin. This tool compound could be used to study the pathophysiology and druggability of ATGL in animal models of metabolic disease and cachexia. Abstract : In this study, we designed and synthesized six series of Atglistatin derivatives from Atglistatin. Compound9e showed potent ATGL inhibitory activity in vitro, which was much stronger than that of Atglistatin, and its inhibitory activity in vivo was similar to that of Atglistatin. Compound9e would be applied to the research and development of adipose triglyceride lipase inhibitor.